Self-Concept of People with HIV (PLHIV) - Miskijan Miskijan; Wahyuningsih Wahyuningsih; Lia Endriyani (Alma Ata University Press, 2017)
HIV AIDS is one of contagion that is caused by virus of HIV which until now there is no medicine or vaccination found. The amount of HIV AIDS patients in Srandakan District are 0,03% of the total population, every year is always increasing 0,01%. Some problems that happened to ODHA in Srandakan Districti.e.an ODHA who moved because always becoming treding talk. An ODHA woman with her two children that is left by her husband when she is going to give birth the second. An ODHA shemale who lived alone. An ODHA man who is stopped from his work with the reason that the office can’t give salary. Toward the condition of ODHA caused some ODHA fell afraid interacting to society around.the aim of this research is getting figure of personal concept toward HIV AIDS in the district of Puskesmas Srandakan Bantul. This research uses qualitative descriptive method. The sample in this research is six people who lived in the Puskesmas Srandakan region and have been took using sampling purposive technic. The conclusion of this research succeded to identify the existence of personal concept problem toward six participants they felt decresing of thinking process, easy to feel tired, worried about don’t get job that causes he can’t fulfill his family need. Worried that HIV status is known by family and society. Changing personal concept about personal identity i.e. ODHA felt comfortable with changing himself from male to be female, worried to find soulmate. Concept to body image that is shame with skin injury. Personal concept of role performance is more roles in-house family, self-limiting toward society. Personal concept of personal esteem is about low personal esteem.